CONSUMER BEHAVIOR AND ITS ROLE IN THE GROWTH OF INDONESIA’S ELECTRIC VEHICLE INDUSTRY - Grace Virginia Latif; Laurentius Beta Wijanarko Pranoto; Orpha Jane (Program Sarjana Manajemen Universitas Internasional Batam, 2026)
The rapid development of Indonesia’s electric vehicle (EV) industry has increased the importance of understanding consumer behavior in the adoption process. This study examines behavioral factors associated with EV adoption in Indonesia through a qualitative thematic analysis of secondary data, including academic literature, policy documents, industry reports, and institutional publications, complemented by expert validation. The analysis identifies five recurring themes: perceived benefits, perceived risks, social influence, brand trust, and incentives. The findings suggest that Indonesian consumers primarily evaluate EVs based on operational efficiency, ownership costs, convenience, and perceived value, while concerns regarding affordability, charging infrastructure, technological reliability, and resale value continue to constrain adoption. By synthesizing evidence from diverse sources, this study provides a context-specific understanding of behavioral considerations relevant to Indonesia’s transition toward sustainable mobility.